Pengembangan Sistem Pelaporan Gangguan Berbasis Web dengan menggunakan Teknologi Progressive Web Application (Studi Kasus: Unit IT PT. Kereta Api Indonesia Daerah Operasi III Cirebon) - Ari Setiawan; Denny Sagita Rusdianto; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The mission of PT. KAI is conducting business activities based on 4 main pillars, namely safety, punctuality, service and comfortability. To reach these 4 pillars, the IT unit of PT. KAI operating area III Cirebon makes a procedure for handling distrubance. But this procedure is still done conventionally, so that it still has several problems such as frequent reports of disturbances that are not successfully delivered, lack of information about officers who are on duty, officers unable to report to the leader when they want to go to place of distrubance and there are no reports of device coming out of the warehouse. To deal with this problem a solution was formed in the form of a system that has the main features disturbance reporting, disturbance handling and warehouse management. Research begins with requirement engineering which analyzed to 48 functional requirements and 1 non-functional requirement. The next step is to make a design and implementation. This system is developed using PHP, JavaScript, CSS and HTML using MVC design patterns (Model, View, Controller) based on web. This system is equipped with progressive web application technology. This system uses a MySQL database. After implementation is finished, testing of the system is carried out. This system has been successfully tested with unit testing, integration testing, validation testing and compatibility testing. The results of the system test is 100% valid for all tests, which means the system is compatible with analysis and design result.